2013
DOI: 10.2215/cjn.11601112
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Structural and Functional Neuroimaging Findings in Children and Adults with CKD

Abstract: Summary CKD has been linked with cognitive deficits and affective disorders in multiple studies. Analysis of structural and functional neuroimaging in adults and children with kidney disease may provide additional important insights into the pathobiology of this relationship. This paper comprehensively reviews neuroimaging studies in both children and adults. Major databases (PsychLit, MEDLINE, WorldCat, ArticleFirst, PubMed, Ovid MEDLINE) were searched using consistent search terms, and studies published betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 47 publications
1
54
0
Order By: Relevance
“…Authors of these studies did not investigate the effect of the specific dialysis modality on spontaneous brain activity in patients with ESRD, because they included patients undergoing hemodialysis and PD and those not undergoing dialysis. In addition, most previous studies have been focused on abnormal gray and white brain matter structures (16,(22)(23)(24)(25)(26). Several studies (2,7,8) included patients with ESRD undergoing hemodialysis and PD, which can have a confounding effect on the study results.…”
Section: Resultsmentioning
confidence: 99%
“…Authors of these studies did not investigate the effect of the specific dialysis modality on spontaneous brain activity in patients with ESRD, because they included patients undergoing hemodialysis and PD and those not undergoing dialysis. In addition, most previous studies have been focused on abnormal gray and white brain matter structures (16,(22)(23)(24)(25)(26). Several studies (2,7,8) included patients with ESRD undergoing hemodialysis and PD, which can have a confounding effect on the study results.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have reported brain atrophy and WMH burden in patients with CKD or renal failure . A meta‐analysis of numerous structural and functional neuroimaging studies that examined children and adults with CKD identified several clear trends, including cerebral atrophy, WMH, cerebral infarction, microbleeding, and cerebral blood flow pattern with affective disorders . In the retrospective population‐based Rotterdam Scan Study, subjects with low eGFR had smaller brain and deep WM volumes and more WMH .…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong graded cross- sectional relation between eGFR and cognitive function in patients with CKD as renal function declines below eGFR of 60 ml/min/1.73 m 2 [25]. Previous structural magnetic resonance imaging (MRI) studies in non-dialysis CKD patients have reported variable prevalence of vascular pathologies and concomitant global and region-specific atrophy [69], in part due to substantive differences in patient populations and range of CKD severity. Most CKD cohort studies have primarily included patients with mild CKD (Stage 3a: eGFR 45–59 ml/min/1.73 m 2 ) rather than those with lower renal function (Stages 3b-5: eGFR <45 ml/min/1.73 m 2 ) who are at higher risk of both cognitive impairment and brain pathology.…”
Section: Introductionmentioning
confidence: 99%